PENDIDIKAN BEBAS BIAYA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH/MADRASAH - Winarsih, Sri (IAIN Ponorogo, 2014)
Abstract: Cost isflow of resource, calculated in set of monetary which released to buy or pay inventory,service, labor,product, equipment and other goods, used for business or others interest. Education is process where someone obtain to get knowledge (knowledgeacquisition), developing skill or ability (development skill) attitude or change attitude. Education is a process of studentâs transformationin order to reach certain things as effect of follow education. Cost of education consist of (1).Direct cost is the expense from parent to learn, example: cost of the text book,practice etc.(2).Indirect costis the expense from parent, people or governmentwhich indirect relate to learning process, for example: levyingthe building, public utilities, canteen, school health unit, etc.Ù ÙØ®Øµ:Â Ø§ÙØªÙØ§ÙÙÙ ÙÙ Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙÙ ØØ³ÙØ¨Ø© ÙÙ ØØ³Ø§Ø¨ Ø§ÙØ¹Ù ÙØ© Ø§ÙÙ ØªØµØ±ÙØ© ÙÙØ¨ÙØ¹ Ø£Ù Ø¯ÙØ¹ Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙÙ Ø¹Ø¯Ø©Ø ÙØ§ÙØ¹Ù ÙØ ÙØ§ÙØ¹Ù ÙØ§ÙØ ÙØ§ÙØ§ÙØªØ§Ø¬Ø ÙØ§ÙØ£Ø¯ÙØ§ØªØ ÙØºÙØ±ÙØ§ Ù Ù Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙÙ Ø³ØªØ¹Ù ÙØ© ÙÙ ØµÙØØ© Ø§ÙØªØ¬Ø§Ø±Ø© Ø£Ù ØºÙØ±ÙØ§. ÙØ§ÙØªØ±Ø¨ÙØ© ÙÙ Ø¹Ù ÙÙØ© ÙØØµÙ ÙÙÙØ§ Ø§ÙÙ Ø±Ø¡ Ø¹ÙÙ Ø§ÙÙ Ø¹Ø§Ø±Ù ÙØ§ÙÙ Ø¹ÙÙÙ Ø§ØªØ ÙØªÙÙ ÙØ© Ø§Ø³ØªØ¹Ø¯Ø§Ø¯Ø§ØªÙ ÙÙÙØ§Ø¡Ø§ØªÙØ ÙØ³ÙÙÙÙØ§ØªÙ. ÙØ§ÙØªØ±Ø¨ÙØ© ÙØ°ÙÙ Ø¹Ù ÙÙØ© Ø§ØµÙØ§Ø Ø§ÙØªÙØ§Ù ÙØ° ÙÙØØµÙ Ø¹ÙÙ Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙØ®Ø§ØµØ© ÙØªÙØ¬Ø© Ø¹Ù ÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØªÙ Ø§ØªØ¨Ø¹ÙØ§. ÙØ«Ù Ø© ØªÙØ§ÙÙÙ ØªØ±Ø¨ÙÙØ© ÙÙÙ : 1) Ø§ÙØªÙØ§ÙÙÙ Ø§ÙÙ Ø¨Ø§Ø´Ø±Ø©Ø ÙÙ Ø§ÙØªÙØ§ÙÙÙ Ø§ÙØªÙ Ø¯ÙØ¹ÙØ§ Ø§ÙØ·Ø§ÙØ¨ Ø£Ù ÙØ§ÙØ¯Ø§Ù ÙÙ ÙÙ Ø© Ø¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙ ÙØ§ÙØªØ¹ÙÙÙ Ø ÙØ¹ÙÙ Ø³Ø¨ÙÙ Ø§ÙÙ Ø«Ø§Ù ÙØ´Ø±Ø§Ø¡ Ø§ÙÙØªØ¨Ø ÙØ§ÙØªØ±Ø¨ÙØ© Ø§ÙØªØ¯Ø±ÙØ¨ÙØ© ÙØºÙØ±ÙØ§Ø 2) Ø§ÙØªÙØ§ÙÙÙ ØºÙØ± Ø§ÙÙ Ø¨Ø§Ø´Ø±Ø©Ø ÙÙÙ Ø§ÙØªÙ ÙØ¯ÙØ¹ÙØ§ Ø§ÙØ·Ø§ÙØ¨ Ø£Ù ÙØ§ÙØ¯Ø§ÙØ Ø£Ù Ø§ÙÙ Ø¬ØªÙ Ø¹Ø Ø£Ù Ø§ÙØÙÙÙ Ø© ÙÙÙ ÙÙ Ø© Ø§ÙØªÙ ÙØ§ ØªØ±ØªØ¨Ø· Ù Ø¨Ø§Ø´Ø±Ø© Ø¨Ø¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙ ÙØ§ÙØªØ¹ÙÙÙ Ø Ù Ø«Ù Ø§ÙØªÙØ§ÙÙÙ ÙØ¨ÙØ§Ø¡ Ø§ÙÙ Ø¯Ø§Ø±Ø³Ø Ø£Ù Ø§ÙÙØ³Ø§Ø¦Ù Ø§ÙØ¹Ø§Ù Ø©Ø Ø£Ù Ø§ÙÙ ÙØµÙ ÙÙÙ ØµØ¯Ø±Ø³Ø©Ø Ø£Ù Ø¹ÙØ§Ø¯Ø© Ø§ÙØµØØ© ÙØºÙØ±ÙØ§.Â Keywords: Pendidikan, bebas biaya, mutu, sekolah.